PENGEMBANGAN ELEKTRONIK LEMBAR KERJA PESERTA DIDIK (E-LKPD) DENGAN PENDEKATAN KONTEKSTUAL PADA SISWA KELAS V SD NEGERI 1 SUNGAI ARE - Arindo Setiawan; Dessy Wardiah; Eni Heldayani (Jurnal Tunas Pendidikan, 2025)
The purpose of the study, namely to develop learning tools, so that students are more active and the teacher as a facilitator. The formulation of the research problem is How to Develop Electronic Learner Worksheets (E-LKPD) with a Contextual Approach? This research method uses the research and development method with the research limits of expert assessment and practicality. Expert assessment is carried out on media, language, and material experts, while practicality with teachers and students. Data collection techniques used documentation and questionnaires, while data analysis techniques used percentages. The results of the study stated that the validity test of E-LKPD with CTL approach in grade V learning of SD Negeri 1 Sungai Are was declared valid and received a score of 81.90%. The practicality test of E-LKPD with the CTL approach in fifth grade learning at SD Negeri 1 Sungai Are was declared very practical and received a score of 89.77%. The effectiveness test of E-LKPD with the CTL approach in learning grade V SD Negeri 1 Sungai Are was declared very effective and received a score of 85.84%.